Demonstration of vertical transmission of Streptococcus suis in swine by genomic fingerprinting. - Amass, S F (1997)
Isolates of Streptococcus suis serotype 5 collected from three sows and nine of their pigs at birth were analyzed by genomic DNA fingerprinting. The cleavage patterns of DNA from S. suis isolated from the sows matched the cleavage patterns of DNA from S. suis isolated from their respective pigs.